Examining the Gap Between Prosecutor Attitudes and Decisions: Case Prioritization Through Case Elimination Mechanisms in Driving With a Suspended License Cases - Arndt, Maria E. (Criminal justice review, 2022)
Prosecutors are granted considerable discretion, particularly for misdemeanors. The current study assesses the processing of misdemeanor driving with suspended license (DWSL) cases. Using interview and administrative data from a Florida jurisdiction, the study first examines prosecutorial attitudes about case elimination mechanisms—declination, dismissal, and diversion—then evaluates the extent to which prosecutors’ views about handling DWSL cases and racial disparities in the legal system are reflective of case processing outcomes. Results indicate prosecutors view case prioritization as important, though it is unclear how they achieve it. Despite a reluctance to decline cases when the elements of an offense are supported by evidence, prosecutors acknowledge they cannot pursue all offenses if there is only marginal public safety return. Contemporaneous administrative data show that DWSL cases were routinely pursued in 2017: nearly all DWSL cases were filed, a third were dismissed, and 11% were diverted. Regression analysis also demonstrates that prosecutors’ views on racial and ethnic disparities are somewhat aligned with the case processing decisions for DWSL cases processed in 2017. These findings are discussed in terms of their implications for prosecutorial policy, practice, and the effects of prosecutorial discretion for low-level cases on communities.